Spanish Mystic of the 16th Century and the “Spiritual Canticle” of Saint John of the Cross - Maria Yu. Ignatieva (Oganissian) (Studia Litterarum)
The article analyzes the poetics of the “Spiritual Canticle” of St. John of the Cross as a single two-part work, consisting of a poetic text and its prosaic commentary. The “Spiritual Canticle” is one of the masterpieces of Spanish mystical literature of the 16th century. The author of the article describes this literary context, showing the reasons for its emergence and flourishing, the main directions and features, and then proceeds to analyze the poetics of the texts under consideration. The relationship between poetry and prose in the literary legacy of St. John of the Cross is one of the traditional themes of juanística. The article proposes to consider both the one and the other as a manifestation of both the mystical experience and the poetic genius of St. John, without placing the commentary in an auxiliar position in relation to the verses. By interpreting his own poetic text, John creates a new parallel text on the same topic, but in a different genre. Each component has its own internal plot.These two plots, called “lyrical” and “theological,” enter into complex relationships. Thus, “mountains,” “forests,” “extraordinary islands” and other images change their meaning both in verses and in commentary, revealing a general but whimsical transformation of an earthly topos into a transcendental one. Transformation takes place through various types of intersection of created and uncreated beginnings: in man, in nature and in God. Poems from lyrics become sacred text, commentary from didactic becomes exegetical.